From editors - Berti Filho, Evoneo; Vettorazzi, Carlos Alberto; Oliveira, Rogerio Goularte Moura Gomes de (REVISTA DE AGRICULTURA, 2017)
From this volume 92 on, Brazilian Journal of Agriculture is the new denomination of the formerly Revista de Agricultura, founded in 1926 by the Professors Nicolau Athanassof, Octavio Domingues and Salvador de Toledo Piza. The Revista de Agricultura was a pioneer one regarding the publication of scientific papers in Brazil. Evoneo Berti Filho Carlos Alberto Vettorazzi Rogério Goularte Moura Gomes de Oliveira